2018
DOI: 10.1021/acs.jmedchem.8b01005
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Matrix Metalloproteinase-9 (MMP-9) as a Novel Target for Treatment of Diabetic Foot Ulcers in Humans and Discovery of a Potent and Selective Small-Molecule MMP-9 Inhibitor That Accelerates Healing

Abstract: Diabetic foot ulcers (DFUs) are a significant health problem. A single existing FDA-approved drug for this ailment, becaplermin, is not standard-of-care. We previously demonstrated that upregulation of active matrix metalloproteinase (MMP)-9 is the reason that the diabetic wound in mice is recalcitrant to healing and that MMP-8 participates in wound repair. In the present study, we validate the target MMP-9 by identifying and quantifying active MMP-8 and MMP-9 in human diabetic wounds using an affinity resin t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
134
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 109 publications
(137 citation statements)
references
References 37 publications
(91 reference statements)
3
134
0
Order By: Relevance
“…We have previously reported the detrimental role of MMP‐9 and the beneficial role of MMP‐8 in wound healing of diabetic mice . We also identified active MMP‐8 and MMP‐9 in human DFUs, with >30‐fold higher active MMP‐9 levels in diabetic patients with more severe and infected ulcers . In support of the detrimental role of MMP‐9, we found that aclerastide, an angiotensin II analog that stimulates NADPH oxidase to mediate cell growth, increases active MMP‐9 levels that may have played a role in aclerastide's clinical failure .…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…We have previously reported the detrimental role of MMP‐9 and the beneficial role of MMP‐8 in wound healing of diabetic mice . We also identified active MMP‐8 and MMP‐9 in human DFUs, with >30‐fold higher active MMP‐9 levels in diabetic patients with more severe and infected ulcers . In support of the detrimental role of MMP‐9, we found that aclerastide, an angiotensin II analog that stimulates NADPH oxidase to mediate cell growth, increases active MMP‐9 levels that may have played a role in aclerastide's clinical failure .…”
Section: Discussionsupporting
confidence: 66%
“…We have previously reported the detrimental role of MMP‐9 and the beneficial role of MMP‐8 in wound healing of diabetic mice . We also identified active MMP‐8 and MMP‐9 in human DFUs, with >30‐fold higher active MMP‐9 levels in diabetic patients with more severe and infected ulcers .…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations